THE EFFECT OF ACADEMIC ABILITY AND ACTUALIZATION DESIGN ON THE RESULTS OF THE ACTUALIZATION OF BASIC TRAINING PARTICIPANTS FOR CIVIL SERVANTS CANDIDATES AT THE REGIONAL HUMAN RESOURCES DEVELOPMENT AGENCY OF CENTRAL JAVA PROVINCE - Alaziz, Muhammad; Rukmini, Rukmini (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to determine the effect of academic ability and actualization design on the results of the actualization of the CPNS Basic Training participants at BPSDMD Central Java Province. The analytical tool used is multiple linear regression, t-test, F test, and coefficient of determination. The number of samples as many as 399 participants were taken by purposive sampling technique. The results of the study concluded that: 1) Academic ability had a positive but not significant effect on the results of the implementation of the actualization of the CPNS Basic Training participants at BPSDMD Central Java Province; 2) The actualization design has a positive and significant impact on the results of the actualization implementation for the participants of the CPNS Basic Training at BPSDMD Central Java Province; 3) Academic Ability and Actualization Design simultaneously have a positive and significant impact on the Results of the Implementation of the Actualization of CPNS Basic Training participants at BPSDMD Central Java Province; 4) The actualization design significantly positively moderates (strengthens) the relationship between the influence of academic ability on the results of the implementation of the actualization of CPNS Basic Training participants at BPSDMD Central Java Province. The recommendations given are 1) For State Administration Institutions to conduct a more in-depth study or evaluation related to the correlation between the provision of academic material that results in the participants' academic abilities and the implementation of actualization; 2) For the Central Java Province BPSDMD to conduct a study or evaluation of the implementation of the CPNS Basic Training comprehensively and to make an evaluation instrument for the role of the coach; 3) For other researchers, the results of this study can be developed both in terms of location and research variables; 4) For Civil Servants (PNS)to keep trying to find the formulation of effective learning methods and for coaches to continue to improve their role to be more effective.